Novel regulation of PLCζ activity via its XY-linker - Nomikos, Michail (Portland Press Ltd., 2011)
The XY-linker region of somatic cell PLC (phospholipase)-β, -γ, -δ and -ϵ isoforms confers potent catalytic inhibition, suggesting a common auto-regulatory role. Surprisingly, the sperm PLCζ XY-linker does not mediate auto-inhibition. Unlike for somatic PLCs, the absence of the PLCζ XY-linker significantly diminishes both in vitro PIP(2) (phosphatidylinositol 4,5-bisphosphate) hydrolysis and in vivo Ca(2+)-oscillation-inducing activity, revealing evidence for a novel PLCζ enzymatic mechanism.